Bidirectional modulation of Alzheimer’s disease via gut microbiota: rescue by fecal transplantation from healthy donors and aggravation by colitis-associated dysbiosis - Zhou, Chenglong; Feng, Xin; Liu, Huina; Cai, Ting; Li, Yihong; Fan, Huadong (Frontiers in Neuroscience, 2025)
IntroductionEmerging evidence implicates gut microbiota dysbiosis as a key modulator for the pathogenesis of Alzheimer’s disease (AD) via the gut-brain axis. To investigate the causal role of microbial communities in AD progression, we performed fecal microbiota transplantation (FMT) in APP/PS1 transgenic mice using donor microbiota from healthy wild-type mice or dextran sulfate sodium (DSS)-induced colitis mice.MethodsCognitive function, amyloid-beta (Aβ) pathology, and pro-inflammatory cytokine levels were assessed in mice. 16S ribosomal RNA sequencing of gut microbiota and bioinformatic functional analyses were applied to identify the specific microbial communities potentially involved in AD progression.ResultsFMT-WT mice (fecal microbiota transplantation from healthy wild-type mice) exhibited significant improvements in spatial memory (Morris Water Maze), exploratory behavior (Y-maze), and locomotor activity (Open Field Test), alongside reduced Aβ plaque burden and normalized expression of pro-inflammatory cytokines (IL-6, IL-1β, TNF-α) in both gut and brain tissues. Conversely, FMT-DSS mice (fecal microbiota transplantation from DSS-treated donors) displayed exacerbated cognitive deficits, heightened Aβ deposition, and elevated pro-inflammatory cytokine levels. Microbial profiling revealed stark contrasts: FMT-WT mice harbored beneficial taxa (Bacteroides, Lachnospiraceae) linked to anti-inflammatory products like short-chain fatty acid, while FMT-DSS mice showed blooms of pathogenic genera (Erysipelatoclostridium, Enterobacteriaceae) associated with neurotoxic metabolites. Functional analyses predicted enrichment of neuroprotective pathways (e.g., lysine metabolism) in FMT-WT and pro-inflammatory pathways (e.g., carbon metabolism) in FMT-DSS. Crucially, neuroinflammation occurred independently of gut barrier disruption, implicating circulating microbial metabolites as key mediators.DiscussionOur findings demonstrate that gut microbiota composition bidirectionally influences AD progression, with FMT from healthy donors attenuating neuroinflammation and pathology, while colitis-associated dysbiosis exacerbates disease hallmarks. Our study positions microbiota-targeted therapies as a promising strategy to modulate AD progression through the gut-brain axis.